STRATEGI GURU BIMBINGAN KONSELING DALAM PENANGGULANGAN FENOMENA PERUNDUNGAN DI SEKOLAH MENENGAH PERTAMA NEGERI 15 KOTA BENGKULU - Lestari, Yusnia; Ledyawati (JURNAL ILMIAH IDEA, 2023)
This study aims to analyze the strategies used by guidance and counseling teachers in dealing with the phenomenon of bullying at SMP Negeri 15 Bengkulu City. This study uses a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The data obtained was then analyzed using data analysis techniques according to Miles and Huberman, namely data reduction, data exposure and drawing conclusions. The results showed that guidance and counseling teachers at Public Junior High School 15 Bengkulu City have been able to adapt to different approaches depending on the characteristics of the students they are handling and have been able to pay attention to the individual needs of students and use strategies that suit their needs. The teacher has also carried out several steps in order to be able to achieve the goal of tackling the phenomenon of bullying and to distribute regular sociometric questionnaires to students to be able to find out how interactions occur with students as an effort to minimize bullying that occurs. In integrating with all stakeholders at Public Junior High School 15 Bengkulu City, guidance and counseling teachers adopt a collaborative approach that involves all parties in dealing with bullying. However, for the maintenance of the pattern, guidance and counseling teachers have not been able to do it, but only use patterns that already existed before. Even though pattern maintenance is an effective strategy in overcoming the phenomenon of bullying in schools, it needs to be carried out on an ongoing basis and not only done once or depending on one strategy.